1995
DOI: 10.1128/mcb.15.6.3327
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Regulation of Ribosomal Component Synthesis in Acanthamoeba castellanii: 5S RNA Transcription Is Down Regulated during Encystment by Alteration of TFIIIA Activity

Abstract: Transcription of large rRNA precursor and 5S RNA were examined during encystment of Acanthamoeba castellanii. Both transcription units are down regulated almost coordinately during this process, though 5S RNA transcription is not as completely shut down as rRNA transcription. The protein components necessary for transcription of 5S RNA and tRNA were determined, and fractions containing transcription factors comparable to TFIIIA, TFIIIB, and TFIIIC, as well as RNA polymerase III and a 3-end processing activity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…TFIIIB/D and TFIIIB/C/D complexes could be similar in size and shape but differ by a small number of polypeptides. Detection of TFIIIB binding to polymerase III templates by gel retardation or DNase I footprinting has been reported previously only for S. cerevisiae (21,23,24), despite the chromatographic resolution of TFIIIB activity in a variety of other systems: mammalian cells (43,57,66), Xenopus laevis (16,46), Drosophila melanogaster (3), and Acanthamoeba castellanii (30). Two kinds of experiments provide indirect evidence for TFIIIB binding in nonyeast systems, however.…”
Section: Discussionmentioning
confidence: 99%
“…TFIIIB/D and TFIIIB/C/D complexes could be similar in size and shape but differ by a small number of polypeptides. Detection of TFIIIB binding to polymerase III templates by gel retardation or DNase I footprinting has been reported previously only for S. cerevisiae (21,23,24), despite the chromatographic resolution of TFIIIB activity in a variety of other systems: mammalian cells (43,57,66), Xenopus laevis (16,46), Drosophila melanogaster (3), and Acanthamoeba castellanii (30). Two kinds of experiments provide indirect evidence for TFIIIB binding in nonyeast systems, however.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the inactivation of rDNA transcription during encystment of Acanthamoeba castellanii demonstrated that inactivation was the result of a modification of RNA polymerase I (52,53). Similarly, studies on the regulation of rDNA transcription in mammalian cells undergoing serum starvation or P1798 cells exposed to DEX demonstrated that a polymeraseassociated factor was responsible for the inhibition of rDNA transcription.…”
Section: Fig 4 Cycloheximide (Chx) Inhibits the Interaction Betweenmentioning
confidence: 99%
“…In contrast, viral infection and serum factors have been shown to alter the activity of the TFIIIC fraction (33,34). Recently the differential expression of the 5 S rRNA and tRNA genes during encystment in Acanthamoeba castellanii has been attributed to the disappearance of the 5 S rRNA-specific transcription factor TFIIIA (35).…”
mentioning
confidence: 99%